Coordenador pedagógico: contribuições para sua formação - Giovani, Priscila de (2013)
The present research, which bears a qualitative nature, has as its centre the investigation of the importance of pedagogical coordinators education, united to this intriguing question: in which conditions can the education and training of these professionals contribute to their performance as managers? Many pedagogical coordinators assume this function, even when they lack specific knowledge on the area. Therefore, training and education to qualify their actions have become a great need. The theme of this dissertation refers to the education and training of the professionals who educate and train teachers: the pedagogical coordinator. The specific objectives are: to present a brief history of teachers education in Brazil and the role played by pedagogical coordinators in this field; to investigate conditions to improve their education and training; to contribute to an educational system that plans actions to support their work. In order to achieve these aims, the research has been bibliographical (to establish a theoretical support), documental (to understand the history of teachers education and training in the chosen city) and has involved data collection, through interviews and questionnaires. The research subjects were pedagogical coordinators of ENSINO FUNDAMENTAL I in the city of Santo André - SP, who held this position in 2012 and the City's Education Director in 2013. The results show that continuous education is essential to the pedagogical coordinators professional development, since they are in charge of teachers education and training. The dissertation analyses characteristics that the education and training of pedagogical coordinators could have and the contents needed for this development, such as strategies of coordinators education and training, the guarantee of practical appliance of theoretical contents, later thinking, the exchange of knowledge between colleagues, homology of processes, among other elements which favor pedagogical coordinators education and training